The Influence of Overconfidence on Auditors and Its Impact on Audit Decision Making: A Systematic Literature Review - Diendha Annisa Nur Attaullah; Yusnaini Yusnaini (Indo Publishing, 2026)
This study examines the influence of overconfidence bias on auditors and its impact on audit decision-making using a Systematic Literature Review (SLR) approach. A total of 22 articles published between 2021 and 2025 were systematically selected from Scopus-indexed and SINTA-accredited journals. The findings show that audit risk is the most frequently examined dependent variable (59.1%), while managerial and CEO overconfidence is the most dominant independent variable (45.5%). The results reveal two contrasting patterns: overconfidence in client management tends to increase audit risk, audit fees, and the likelihood of financial misstatements, whereas overconfidence within auditors reduces professional skepticism and compromises audit quality. These findings indicate that the impact of overconfidence on audit outcomes depends significantly on whether it originates from the auditor or from client management. This study contributes to the behavioral auditing literature by synthesizing existing empirical evidence and identifying directions for future research.